Brand Image Terhadap Customer Loyalty melalui Customer Satisfaction pada Pengguna Produk Tupperware di Kota Bandung - Angelita Permatasari Pardede; Rosmini Ramli (IPM2KPE, 2024)
This research aims to evaluate the impact of brand image dimensions on customer loyalty through customer satisfaction regarding Tupperware brand food & beverage container products, especially in the city of Bandung. Data collection was carried out through interviews with respondents aged 17-40 years and who had experience using and purchasing Tupperware products. Participation in this research involved 90 respondents using cross-sectional data collection techniques or one shot study. Data analysis used a quantitative descriptive approach, normality test, multiple linear regression, and Sobel test with the help of statistical software program of social science (SPSS) version 26. Of the ten hypotheses proposed, eight of them were strengthened by empirical findings. These results indicate that customer satisfaction can act as a link between the impact of brand image dimensions (brand strength, brand uniqueness, and brand liking) and customer loyalty. In conclusion, this research can provide benefits for companies and management related to Tupperware products and similar food & beverage container industries in developing relevant strategies to improve the quality of these attributes. Keywords: Brand Image, Customer Satisfaction, Customer Loyalty